Kontrol' tekhnicheskoi i takticheskoi podgotovlennosti v gornolyzhnom sporte: problema i rezhenie - Lisovsky, A. F. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this lecture was to analyse the problem of the technical and tactical preparadeness control in mountain skiers. The classification of the technical manners in mountain skiing was elaborated as well as the parameters of the standard skiing routes for the evaluation of the mountain skiers' technical-tactical preparadeness.